2006
DOI: 10.1073/pnas.0602571103
|View full text |Cite
|
Sign up to set email alerts
|

A common allosteric site and mechanism in caspases

Abstract: We present a common allosteric mechanism for control of inflammatory and apoptotic caspases. Highly specific thiol-containing inhibitors of the human inflammatory caspase-1 were identified by using disulfide trapping, a method for site-directed small-molecule discovery. These compounds became trapped by forming a disulfide bond with a cysteine residue in the cavity at the dimer interface Ϸ15 Å away from the active site. Mutational and structural analysis uncovered a linear circuit of functional residues that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
161
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 27 publications
(21 reference statements)
11
161
0
1
Order By: Relevance
“…5A). Recent studies of caspase-1 and caspase-7 revealed that compounds targeting the dimerization interface, Ϸ15 Å away from the active site, can propagate structural changes that ultimately deform the active sites (19,20). Perhaps the most convincing observation from our work in support of this conjecture emerges from the fact that the ␤6 interface is the most conserved element among all of the regions of contact between FLIP and z-C8 (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…5A). Recent studies of caspase-1 and caspase-7 revealed that compounds targeting the dimerization interface, Ϸ15 Å away from the active site, can propagate structural changes that ultimately deform the active sites (19,20). Perhaps the most convincing observation from our work in support of this conjecture emerges from the fact that the ␤6 interface is the most conserved element among all of the regions of contact between FLIP and z-C8 (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, our data suggest new approaches for inhibiting AdoMetDC in trypanosomes, either by blocking formation of the AdoMetDC-prozyme complex and/or by stabilizing the inactive conformation of AdoMetDC. Successful strategies for these approaches have recently been described for other proteins (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed how phosphorylation of caspase-6 at Ser-257 results in a steric clash of as few as three atoms in the side chain of Pro-201, which leads to allosteric inhibition by preventing the active conformation of one loop. In caspase-7 (45,63,64) or -1 (65,66), binding small synthetic allosteric inhibitors at the dimer interface leads to a series of side chain conformational changes that ultimately block the substrate-binding groove, preventing proteolytic activity. These examples and a great number of other examples from a large number of proteins are satisfying as it is possible to visualize the series of side chain conformational changes that lead to inactivation.…”
Section: Discussionmentioning
confidence: 99%